Relative concerns and delays in bargaining with private information - Ana Mauleon; Vincent Vannetelbosch (Games, 2013)
We consider Rubinstein's two-person alternating-offer bargaining model with two-sided incomplete information. We investigate the effects of one party having relative concerns about the bargaining outcome and the delay in reaching an agreement. We find that facing an opponent with stronger relative concerns only hurts the bargainer when she is stronger than her opponent. In addition, we show that an increase of one party's relative concerns will decrease the maximum delay in reaching an agreement.
Keywords: 330; relative concerns; alternating-offer bargaining; private information; maximal delays